2017
DOI: 10.1016/j.jceh.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Transient Elastography (Fibroscan) in Patients with Non-cirrhotic Portal Fibrosis

Abstract: Transient elastography (Fibroscan) is significantly low in patients with NCPF compared to patients with cirrhosis. It is a very useful non-invasive technique to differentiate between Child's A cirrhosis and non-cirrhotic portal fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 17 publications
0
21
1
Order By: Relevance
“…The prevalence of HRV in our study is lower than in some other reported series [17, 18]. This may reflect the heterogeneity of causes of NCPH in our patient cohort, as different causes of NCPH may be associated with varying risk of varices or variceal bleeding [6, 19].…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The prevalence of HRV in our study is lower than in some other reported series [17, 18]. This may reflect the heterogeneity of causes of NCPH in our patient cohort, as different causes of NCPH may be associated with varying risk of varices or variceal bleeding [6, 19].…”
Section: Discussioncontrasting
confidence: 68%
“…The number of patients with HRV in this cohort however was very small. LSM has been proposed as an adjunctive tool to distinguish between cirrhosis and idiopathic NCPH as the values are generally higher than healthy controls but lower than matched patients with cirrhosis [17, 18]. Complicating the issue is the diverse range of causes of NCPH.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive methods, in particular US elastography, are very helpful for diagnosing PSVD with portal hypertension 8 (i.e., INCPH), as normal or only slightly increased LSM (i.e., < 10 kPa for VCTE) indicates the absence of ACLD. [128][129][130] In these patients, the presence of specific (varices, portal hypertensive bleeding, portosystemic collaterals) and nonspecific signs of portal hypertension (PLT < 150G Â L À1 , or spleen size ! 13 cm) is suggestive of prehepatic or intrahepatic presinusoidal causes of portal hypertension, which are both situations in which HVPG underestimates the severity of portal hypertension.…”
Section: Diagnosing Portosinusoidal Vascular Disease With Portal Hypementioning
confidence: 99%
“…We also do not agree with the investigators that among noninvasive tests transient elastography (TE) is inadequate for diagnosis of NCPH. In our recent study, we showed that TE in patients with NCPH was significantly lower compared to patients with cirrhosis, and it correlated well with HVPG. Thus, TE can be a useful noninvasive technique to differentiate between Child's A cirrhosis and NCPH.…”
mentioning
confidence: 77%